1998
DOI: 10.1128/aem.64.7.2545-2553.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective PCR Protocol for Detecting 16S rRNA Genes of the Genus Pseudomonas (Sensu Stricto) in Environmental Samples

Abstract: Pseudomonas species are plant, animal, and human pathogens; exhibit plant pathogen-suppressing properties useful in biological control; or express metabolic versatilities valued in biotechnology and bioremediation. Specific detection ofPseudomonas species in the environment may help us gain a more complete understanding of the ecological significance of these microorganisms. The objective of this study was to develop a PCR protocol for selective detection ofPseudomonas (sensu stricto) in environmental samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(104 citation statements)
references
References 47 publications
3
98
0
3
Order By: Relevance
“…PCR products from soils, using the Ps-for/Ps-rev, were not obtained when the annealing temperature was 68³C but were present at 65³C. This observation is an agreement with Widmer et al [39].…”
Section: Pcrsupporting
confidence: 91%
See 2 more Smart Citations
“…PCR products from soils, using the Ps-for/Ps-rev, were not obtained when the annealing temperature was 68³C but were present at 65³C. This observation is an agreement with Widmer et al [39].…”
Section: Pcrsupporting
confidence: 91%
“…In this study, and others [39], ampli¢cation using Ps-for/ Ps-rev with soil-extracted DNA as a template could only be achieved when the annealing temperature was lowered to 65³C with resultant lowering of ampli¢cation stringency. Widmer et al [39] showed that 92% of Ps-for/Psrev clones ampli¢ed directly from soil were Pseudomonas in origin, with 2.7% represented by a clone closely related to a Nitrosospira sp. (GenBank accession number AJ012107) which displays three mismatches with Ps-for and two mismatches with Ps-rev.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…(Sampling: EB, raw input; DTI, distribution tank input; D1, disc tank 1; Bio1, biofilm of disc 1; Bio2, biofilm of disc 2; D2, disc tank 2 and SD, output secondary clarifier). and PsR, reported by Widmer et al [21]. The PCR mixture consists of MgCl 2 (2.5 mM), dNTPs (200 mmol), 2.5 U Taq DNA polymerase in 1Â Taq buffer and 20 pmol of each primer.…”
Section: Pcr Amplification Dgge Analysis and Sequencing 231 Pcrmentioning
confidence: 99%
“…For the ammonia oxidisers, the ¢rst round of PCR was carried out using the CTO primers [15] with a cycle of 95 ‡C for 5 min followed by 35 cycles of 95 ‡C for 1 min, 57 ‡C for 1 min, 72 ‡C for 2 min, and a ¢nal extension of 72 ‡C for 10 min. Pseudomonad (sensu stricto) 16S rDNA was ampli¢ed using the primers Ps-for and Ps-rev [16], and the cycle, 95 ‡C for 5 min followed by 35 cycles of 95 ‡C for 1 min, 62 ‡C for 1 min, 72 ‡C for 2 min., and a ¢nal extension time of 10 min at 72 ‡C was employed. The products from the ¢rst round of PCR were then run on a 1% low melting point agarose gel (Roche Diagnostics), stained in ethidium bromide and visualised under ultraviolet light.…”
Section: Pcr Ampli¢cation Of 16s Rdnamentioning
confidence: 99%